Multi-hope relay based high capacity energy efficient model for ultra wideband communication system - Rajanna, B.; Chandrashrkar, P.; KishanRao, K. (International Journal of Engineering and Technology, 2017)
Demanding large bandwidth and signal robustness over a short distance, ultra wideband communication systems plays an important role. UWB systems exhibits very low spectral density, implies that the interference to narrowband systems is very small. The relay based communication has the advantages of coverage extension, range extension, increase data rates and green communication. The relay based communication with UWB frequency is used to increase the coverage area by using of relays and increasing the data rates by increasing SNR of the links using multi-hop communication. In this paper, capacity and bit error rate of relay based UWB system for indoor and outdoor channel models are analyzed. key Terms—UWB, green communication, multi-hop, capacity, bit error rate, spectral density.